Creative leadership from Islamic perspective - Mohammad Hassan Hilal , Huda (2014)
While Ekvall and Arvonen used the three dimensions model of leadership behavior; focus on task, focus on people and a concern for change. They implanted creative leadership on the third dimension which includes: management competencies, leadership strategies and leading at the edge of chaos. The Islamic model builds on Deism concept that insist the oneness of Allah, and its influences on different levels of leadership. The first and foremost consequence to Deism concept is self-liberation from imitation, that resulted in inducing change. Its influence on people and task dimensions might be shown in developing an accountability feeling that leads to transparency in a variety of behaviors. The dimension of change might reflect the insights provided by Deism concept in its three levels. In the first level; management competencies, there are three constituents such as preparing qualified leaders who are oratorical and able to change traditional concepts, and to have positive expectations in individuals, and gaining their agreement. On the other hand, major improvements are required in the second level which should make profound effects. The key for these effects is the quality of interpersonal relationships. The most important level is leading in the edge of chaos because leadership should function in a high anxiety context by using integrative methods to accomplish tasks. Leaders ought to deploy the talented and independent minded companions. As a result; such a creative leadership might lead to establish active and genius communities.